IMPLEMENTASI SISTEM ONLINE PAJAK BUMI BANGUNAN PEDESAAN DAN PERKOTAAN (PBB-P2) : (Studi pada Badan Pendapatan Daerah Kabupaten Belu) - Florisco Portogi Mauk Florisco (Jurnal Administrasi Publik, 2023)
Implementing the Rural and Urban Building Land Tax Online System (Study at Bapenda of Belu Regency). The Public Administration Paradigm through the New Public Management (NPM) and New Public Governance (NPG) emphasizes the services provided by the government to be carried out efficiently and effectively to achieve transparency in improving performance. The research was conducted to analyze the implementation of the Rural and Urban Building Tax Online System (PBB-P2) in Belu Regency using the theory of public policy implementation according to Randall B. Ripley and Franklin (1986) using three indicators, namely the level of apparatus compliance, smoothness and lack of problems, and performance. The research was conducted using a qualitative descriptive research method to identify the extent to which the policy was implemented through Regent Regulation Number 16 of 2021 concerning the Implementation of the Online Regional Tax System in Belu Regency for the type of Rural and Urban Land Building Tax which resulted in the performance of Rural and Urban Land Building Tax revenues not being optimal and not yet optimally on target.